Diagnostic performance of sex hormone binding globulin (SHBG) expression in predicting prostate cancer (PCa) - Lubis, Anggiat Pratama; Danarto, H R; Indrawarman; Yurisal Akhmad Dany; Ery Kus Dwianingsih (Published by Universitas Gadjah Mada, 2024)
Globally, 1.3 million new cases of prostate cancer (PCa) and 359,000 deaths were reported in 2018. Due to rapid population growth and increasing rates of aging worldwide, the PCa has become the 5th leading cause of death in men. Sex hormone binding globulin (SHBG) presents in both men and women and its expression is often associated with the development of PCa and breast cancers. This study was conducted to assess the diagnostic performance of SHBG expression in predicting PCa. A total of 31 patients with PCa and 14 patients with BPH as a control were involved in this study. The SHBG expression of formalin-fixed paraffin-embedded (FFPE) prostate tissue was examined by the quantitative reverse transcriptase polymerase chain reaction (RT-PCR). Receiver operator characteristic (ROC) curves were produced and the area under the curve (AUC) was calculated to evaluate the diagnostic performance of the SHBG expression in predicting the PCa. The AUC of SHBG expression was 0.868 (95% CI 0.764-0.971; p<0.001) which indicated good diagnostic performance. The cutoff value was 6.731 which corresponded to 80% accuracy, 71% sensitivity, and 100% specificity. In conclusion, SHBG expression in prostate cancer tissues could be a molecular marker in PCa diagnosis. ABSTRACT Secara global terdapat 1,3 juta kasus baru kanker prostat (prostate cancer/PCa) dan 359.000 kematian dilaporkan pada tahun 2018. Karena pertumbuhan populasi yang cepat dan meningkatnya angka usia lanjut di seluruh dunia, PCa telah menjadi penyebab kematian utama ke-5 pada pria. Sex hormone binding globulin (SHBG) terdapat pada pria dan wanita dan ekspresinya sering dikaitkan dengan perkembangan PCa dan kanker payudara. Penelitian ini dilakukan untuk menilai potensi SHBG sebagai penanda molekuler dalam diagnosis PCa. Sebanyak 31 pasien PCa dan 14 pasien BPH sebagai kontrol dilibatkan dalam penelitian ini. Ekspresi SHBG dari jaringan prostat formalin-fixed paraffin-embedded (FFPE) diperiksa dengan the quantitative reverse transcriptase polymerase chain reaction (RT-PCR). Receiver operator characteristic (ROC) dihasilkan dan the area under the curve (AUC) dihitung untuk mengevaluasi kinerja diskriminatif ekspresi SHBG dalam diagnosis PCa. AUC ekspresi SHBG adalah 0,868 (95% CI 0,764-0,971; p<0,001) yang menunjukkan kinerja diskriminatif yang baik. Nilai cutoff adalah 6,731 yang berhubungan dengan akurasi 80%, sensitivitas 71% dan spesifisitas 100%. Kesimpulannya, ekspresi SHBG pada jaringan kanker prostat dapat menjadi penanda molekuler dalam diagnosis PCa